Unlawfulness Within the Bugo Tradition in Morotai: A Comparative Perspective of Positive Criminal Law & Islamic Criminal Law - Rahmat Abdullah; Abdul Mutalib; Andri Sutrisno; Agnes Fitryantica; Arikha Saputra (Universitas Islam Negeri Jakarta, 2026)
The Bugo tradition in Sangowo Village, Morotai Island Regency, is the practice of taking fruit or goods from someone's garden by leaving a sign as notification to the owner. This practice raises legal issues when confronted with theft under the Criminal Code and sariqah in fiqh al-jināyāt. This study employs a legal-empirical or socio-legal method with conceptual and comparative approaches to analyse Bugo's legal status from the perspectives of positive and Islamic criminal law. The results show that although Bugo formally fulfills the elements of Article 476 of the Criminal Code, its material unlawfulness is nullified because it is a living law accepted by the community and qualifies as a reason for criminal exemption outside the law. From the fiqh al-jināyāt perspective, Bugo does not fulfill the elements of khufyah and qaṣd al-sariqah, while strong shubhah from ʿurf nullifies the ḥadd based on the rule of